Acquired Immunodeficiency from Maternal Chemotherapy and Severe Primary Pneumocystis Infection in an Infant. (16th March 2020) - Lim, Adeline Yi Ling; Mattke, Adrian Christian; Clark, Julia Elizabeth; Pinzon-Charry, Alberto; Alphonso, Nelson; Kapur, Nitin
Abstract : Pneumocystis jirovecii is recognized as an opportunistic pathogen in immunosuppressed patients. We report a case of severe Pneumocystis pneumonia (PCP) in an infant with acquired combined immunodeficiency secondary to maternal chemotherapy exposure during the second and third trimesters of pregnancy. The infant required cardiorespiratory support with veno-venous extracorporeal membrane oxygenation (VV-ECMO) for severe respiratory failure. This case highlights the potential for severe acquired immunodeficiency in this patient cohort and further postnatal surveillance is highly recommended.